Studies of anion transport through supported liquid membrane - Gaikwad, Abaji G. (Analytical Letters, 2009)
Transport studies of anions were investigated through cellulose triacetate supported liquid membrane. The experimental variables explored were concentration of anions, sodium hydroxide, and stirring speed. The two-channel membrane system has been explored for the transport of carbonate ions from source to receiving phases. Carbonate ions are selectively transported through the cellulose triacetate supported liquid membrane in comparison with that of nitrate and sulfate. Sulfate and nitrate anions are strongly held in the cellulose triacetate membrane, and then stripped out later. Carbonate ions are loosely bound to the cellulose triacetate membrane and stripped out earlier.
Keywords: Anions; cellulose triacetate membrane; solvent effect; stability of supported liquid membrane; two-channel membrane system